The influence of reaction time on non-covalent functionalisation of P3HT/MWCNT nanocomposites - Norli, Abdullah; Norizan, Mohd Nurazzi; Ngah Demon, Siti Zulaikha; Abdul Halim, Norhana; Mohamad, Imran Syakir (MDPI (Multidisciplinary Digital Publishing Institute), 2021)
Non-covalent functionalisation of the carbon nanotube (CNT) sidewall through polymer wrapping is the key strategy for improving well-dispersed CNTs without persistent alteration of their electronic properties. In this work, the effect of reaction time on regioregular poly (3-hexylthiophene2,5-diyl) (P3HT)-wrapped hydroxylated multi-walled CNT (MWCNT-OH) nanocomposites was investigated. Five different reaction times (24, 48, 72, 96, and 120 h) were conducted at room temperature in order to clearly determine the factors that influenced the quality of wrapped MWCNTOH. Morphological analysis using Field Emission Scanning Electron Microscopic (FESEM) and HighResolution Transmission Electron Microscope (HRTEM) analysis showed that P3HT successfully wrapped the MWCNT-OH sidewall, evidenced by the changes in the mean diameter size of the nanocomposites. Results obtained from Raman spectroscopy, X-ray Photoelectron Spectroscopy (XPS) as well as Thermogravimetric Analysis (TGA) showed a significant effect of the wrapped polymer on the CNT sidewall as the reaction time increased. Overall, the method used during the preparation of P3HT-wrapped MWCNT-OH and the presented results significantly provided a bottom-up approach to determine the effect of different reaction times on polymer wrapping to further expand this material for novel applications, especially chemical sensors.